The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12903-019-0782-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical orthodontic treatment on quality of life in Chinese young adults with class III malocclusion: a longitudinal study

Abstract: Background The quality of life in Class III malocclusion patients are worse than those without the disorder and previous studies have shown that surgical orthodontic treatment has a different effect on these patients compared with mild or moderate malocclusion. This study aimed to investigate the changes in quality of life in patients with Class III malocclusion during surgical orthodontic treatment in Chinese young adults. Methods The 14-item Short Form Oral Health Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
1
33
0
3
Order By: Relevance
“…With regard to QoL, this study found that both the onesplint and the two-splint groups experienced significant improvement in OQLQ scores after treatment, which is similar to other studies on East Asian Class III OGS patients [30][31][32]. In addition, despite the worse QoL in the one-splint group pretreatment, there was no significant difference between the two groups in OQLQ post-treatment, suggesting a similar level of QoL was attained.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to QoL, this study found that both the onesplint and the two-splint groups experienced significant improvement in OQLQ scores after treatment, which is similar to other studies on East Asian Class III OGS patients [30][31][32]. In addition, despite the worse QoL in the one-splint group pretreatment, there was no significant difference between the two groups in OQLQ post-treatment, suggesting a similar level of QoL was attained.…”
Section: Discussionsupporting
confidence: 87%
“…Details of the included studies are summarized in Table 1 . Among the 13 prospective before–after studies included, only 3 had a control group composed of: female students at the university who had a normal occlusion ( n = 14) [ 32 ], volunteers aged 19–20 years old attending a nonmedical, specialty university and with no jaw deformities ( n = 96) [ 24 ]; and healthy individuals, mainly patients’ relatives, classmates, or colleagues ( n = 24) [ 33 ]. The final sample size of patients with dentofacial deformities ranged from 14 to 85 subjects, and the mean of age ranged from 21.3 to 31 years.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike, the authors found that there were no statistically significant differences regarding the OHIP-14 values before and after orthodontic treatment. However, most of the authors, who compared the OHIP-14 values before and after orthodontic treatment, found that the patients' quality of life had significantly improved after orthodontic treatment [27][28][29][30]. Moreover, Zheng et al [31] found that the positive impact of orthodontic treatment on the patients' quality of life depends on the type of malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, patients with class II benefitted the most from the space closure stage, whereas patients with class I malocclusion benefitted the most from alignment and levelling of their teeth, which is an initial stage of orthodontic treatment. Ni et al [29] assessed the OHIP-14 in patients with skeletal class III, who had been treated surgically. The authors found that during the decompensation phase of orthodontic treatment, the patients' quality of life had significantly decreased, whereas after the surgical orthodontic treatment, it had been significantly improved.…”
Section: Discussionmentioning
confidence: 99%